Perioperative Management of Neurological Conditions - Manjeet Singh Dhallu; Ahmed Baiomi; Madhavi Biyyam; Sridhar Chilimuri (SAGE Publishing, 2017)
Perioperative care of the patients with neurological diseases can be challenging. Most important consideration is the management and understanding of pathophysiology of these disorders and evaluation of new neurological changes that occur perioperatively. Perioperative generally refers to 3 phases of surgery: preoperative, intraoperative, and postoperative. We have tried to address few commonly encountered neurological conditions in clinical practice, such as delirium, stroke, epilepsy, myasthenia gravis, and Parkinson disease. In this article, we emphasize on early diagnosis and management strategies of neurological disorders in the perioperative period to minimize morbidity and mortality of patients.